PERSEPSI DAN SIKAP BAHASA MASYARAKAT LAMPUNG SELATAN TERHADAP PENGGUNAAN BAHASA INDONESIA DI HARIAN LAMPUNG POST - Ratih Rahayu; Erwin Wibowo (tuahtalino, 2018)
This study aims to determine the perceptions and attitudes of the people of South Lampung language against the use of Indonesian in Daily Lampung Post. The methodology used in this research is quantitative descriptive approach. Analyzed data obtained through direct interviews with respondents. Respondents in this study were 30 of age and a different educational background. Most respondents found Lampung Post is quite appropriate in the use of foreign language vocabulary. Most respondents also argued that the use of foreign languages in Lampung Post will not threaten the position of Indonesian and local languages. From all the answers to the interview questions were given to respondents it can be concluded that the majority of respondents have a positive attitude towards Indonesian. This is evident from the answers of respondents who have the awareness to put Indonesian compared to a foreign language and want the mass media (LampungPost) more attention to the use of the Indonesian language.